2020
DOI: 10.36346/sarjods.2020.v02i01.002
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Considerations in Pulmonary Disorder Patients

Abstract: Oral health is mirror of general health. Oral healthcare professionals must be able to identify patients with systemic diseases, compromising conditions, and disabilities that have an impact on, and can be impacted by, oral and maxillofacial health care. The ability to properly practice dentistry within the context of the larger health care system is often a challenge for the dental practitioner but need not be so. Inappropriate identification of a patient with a compromising systemic condition through imprope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Furthermore, a study conducted by Chinedu U. Ugwumba et al showed that the prevalence of bacteremia associated with tooth extraction after preoperative mouthwash with 0.2% chlorhexidine was significantly lower than when patients had preoperative mouthwash without chlorhexidine [12]. e AHA recommends chlorhexidine or International Journal of Dentistry povidone-iodine mouth rinses whilst the British Society for Antimicrobial Chemotherapy (BSAC) recommends the administration of chlorhexidine gluconate mouth washes 0.2% held for 1 min in mouth, before dental procedures to narrow bacteremia [11,13]. e use of probiotic was proposed to modify the oral environment in recent study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study conducted by Chinedu U. Ugwumba et al showed that the prevalence of bacteremia associated with tooth extraction after preoperative mouthwash with 0.2% chlorhexidine was significantly lower than when patients had preoperative mouthwash without chlorhexidine [12]. e AHA recommends chlorhexidine or International Journal of Dentistry povidone-iodine mouth rinses whilst the British Society for Antimicrobial Chemotherapy (BSAC) recommends the administration of chlorhexidine gluconate mouth washes 0.2% held for 1 min in mouth, before dental procedures to narrow bacteremia [11,13]. e use of probiotic was proposed to modify the oral environment in recent study.…”
Section: Discussionmentioning
confidence: 99%